Will they come back? Evaluation of health student placements in remote and very remote regions of Australia - Robyn Doney; Elyce Green; Alice Munro; James Debenham (BMC Medical Education)
Abstract Background Despite the benefits of rural placements in attracting healthcare professionals to rural areas, there remains a gap in understanding the specific impact of placements in remote and very remote areas of Australia, particularly within the unique context of the Kimberley region. There is a need to elucidate differences across geographical areas and contribute to the knowledge about the specifics of where and how student placement programs work. This research explored the impact of a remote placement program at Majarlin Kimberley Centre for Remote Health (‘Majarlin’) on educational outcomes and workforce intentions of participating students. Methods This research evaluated student placement data and post-placement surveys of allied health, dentistry, midwifery and nursing students who had completed remote placements in the Kimberley region between 2018 and 2024. Placement numbers and demographic data from 2018 to 2023 were descriptively analysed, while post-placement surveys collected between January 2023 and June 2024 were used to examine educational outcomes, placement satisfaction, and rural practice intention. Results Between 2018 and 2023, Majarlin hosted 1111 students from 20 universities in remote and very remote regions, completing a total of 6068 weeks from 2018 to 2023. Post-placement surveys showed high levels of student satisfaction, with 96.2% also reporting improved clinical knowledge. Many students participated in voluntary positions in the community while completing their clinical placements, with 97.1% feeling that they had a positive impact on the community. All students reported that their cultural awareness and ability to engage with Aboriginal and Torres Strait Islander Peoples improved. Notably, intention to work in remote areas significantly increased post-placement (p < .001). Conclusions The results of this study demonstrated that the remote student placement program improved students’ self-rated clinical knowledge, cultural awareness, and community engagement skills. The program significantly influenced students’ intention to work in remote areas after graduation. These results can be used to inform the design and delivery of similar remote student placement programs which aim to improve the rural health workforce pipeline, paving the way for a more equitable and effective healthcare system across Australia.